Complex coacervation for the development of composite edible films based on LM pectin and sodium caseinate. (20th October 2016) - Eghbal, Noushin; Yarmand, Mohammad Saeid; Mousavi, Mohammad; Degraeve, Pascal; Oulahal, Nadia; Gharsallaoui, Adem
Highlights: Complex coacervates between sodium caseinate (CAS) and LM pectin (LMP) were formed at pH 3.0. Charge neutrality occurred for a CAS/LMP ratio corresponding to the maximal coacervation. The formation of complexes had a significant effect on the properties of LMP based films. Mechanically resistant films were produced with a CAS/LMP ratio of 0.05. The produced films can be used to develop active food packaging. Abstract: Coacervation between sodium caseinate (CAS) and low methoxyl pectin (LMP) at pH 3 was investigated as a function of protein/polysaccharide ratio. The highest amount of complex coacervates was formed at a CAS/LMP ratio of 2 at which the ζ-potential value was zero and the turbidity reached its highest value. Then, the properties of films based on these complex coacervates were studied. Coacervation resulted in decreasing water content and water sorption of films as the protein concentration increased. The mechanical properties of films were highly influenced by the formation of electrostatic complexes. The highest values of Young's modulus (182.97± 6.48 MPa) and tensile strength (15.64 ± 1.74 MPa) with a slight increase of elongation at break (9.35 ± 0.10%) were obtained for films prepared at a CAS/LMP ratio equal to 0.05. These findings show that interactions between LMP and CAS can be used to develop innovative packaging containing active molecules.